Analisis Faktor-Faktor Penghambat Kontraktor dalam Penerapan Sistem Manajemen K3 pada Proyek Konstruksi Gedung di Palangka Raya - Corah Malem Br Sinulingga; Dewantoro Dewantoro; Veronika Happy P (Jurnal Serambi Engineering, 2023)
Palangka Raya is capital of Central Kalimantan and continues to grow in the architectural sector. In construction projects, building construction is a profession with a very high risk of accidents during work. Occupational accidents are a daily occurrence and an occupational health and safety management system is essential to prevent accidents and reduce occupational accidents in construction projects. The purpose of this study is to identify barriers to the implementation of SMK3 in Palangka Raya architectural projects. Research Surveys were conducted by distributing questionnaires directly to identified contractors through the Palangka Raya Electronic Procurement Service (LPSE) website. The data obtained were processed with SPSS software and the main model was mean test and standard deviation. According to the analysis, the factors inhibiting SMK3 implementation in the Palangka Raya construction project are statistically: average score of 3.65, standard deviation of 1.051, (2) lack of strict sanctions for workers not applying labor protection, average score of 3.60, standard deviation of 0.744, (3) lack of understanding of occupational health and safety from 3.60 of. 0.810.